Intrahousehold allocation, gender relations, and food security in developing countries - Quisumbing, Agnes R.; Smith, Lisa C. (Cornell University, 2007)
Many important decisions that affect development outcomes are made by households and families. What factors affect the way resources are allocated within the household? Why does the division of rights, resources, and responsibilities within the household matter for food security? This case study focuses on one dimension of the intrahousehold allocation of resources: gender. It begins with a definition of the household and discusses the factors that affect the distribution of resources within the household (including, but not limited to, gender). It then presents empirical evidence from two studies by the International Food Policy Research Institute (IFPRI). The first examines the link between women’s status and child nutrition, using data from nearly 40 developing countries, and the second investigates how the resources that husbands and wives bring to marriage affect household expenditures and child schooling outcomes in four developing countries. This case study then identifies various stakeholders, including men, women, and especially children within families; community leaders, civil society organizations, and development practitioners at the local level; and national-level policy makers and members of the donor community who are interested in eradicating poverty, reducing malnutrition, and improving gender equity. Finally, it suggests two broad policy options to achieve gender equity: (1) eradicating discrimination and (2) promoting active catch-up of women’s status, providing examples of successful programs in Bangladesh, Guatemala, and Mexico. Your assignment is to recommend to the government of a country of your choice how gender aspects should be incorporated in government policy to improve household food security and the nutritional status of women and children.